Importance of the Bio-psychosocial Model of Practice in Health Care Services - Khatri, Pratima; Baniya, Mandira (Journal of Karnali Academy of Health Sciences, 2022)
Background: Bio-psychosocial approach has been considered a multi-dimensional, holistic aspect of health care services. In developing countries, the biopsychosocial approach has a significant role in minimizing the health care cost of the bio-medical approach by dealing person as a whole rather than as a part of the sum. This model deals with the causative agents and various aspects of the personal life such as preventive aspects, lifestyle & behavior modification, environmental factors, host, genetic factors, culture, financial, and interpersonal relationships.Objective: The main aim of this paper is to discuss the importance of the bio-psychosocial approach to healthcare practice in the healthcare services in Nepal.Method: While writing this article, the authors have reviewed the literature through a database and search engine (google scholar, PubMed, and Henari), talked to the patients (face to face interviews), met the family members, and observed the care providers in the hospital and a rehabilitation center.Result: The authors have found practices of the bio-medical approach in the healthcare setting. Cases one and two showed that patients’ health issues were not managed effectively and efficiently only treating them by practicing a biomedical approach. However, both case’s issues were properly addressed after shifting to adopting the biopsychosocial approach. The biomedical approach revealed somehow delays in identifying the root cause of health problems and increases dissatisfaction among service receivers toward the service provider.Conclusion: The need for practicing the bio-psychosocial model for healthcare facilities is imperative to improve the health care outcome, public satisfaction with services, build trust, and minimized the healthcare cost toward health care services in a healthcare setting.